TINGKAT PENGETAHUAN SISWA TENTANG TINDAKAN PERTOLONGAN PERTAMA PADA KECELAKAAN - Rachmadiwansyah, Abang Muhammad Hafidz; Fauzan, Suhaimi; Maulana, Muhammad Ali; Fradianto, Ikbal; Novikadarti R, Gabby (Jurnal Keperawatan dan Kesehatan, 2024)
Emergency situations require immediate action, as indicated by data from the 2018 Basic Health Research (Riskesdas) showing a significant increase in injury rates in Indonesia, including West Kalimantan. Injuries are most common among individuals aged 15-24, with various types such as abrasions, cuts, sprains, and fractures. This research aimed to investigate students' knowledge of first aid measures at Mujahidin High School in Pontianak, with the hope of improving their understanding and preparedness in handling accidents in the school environment effectively. This study used a quantitative descriptive-analytic method with stratified random sampling, involving 245 students from grades X and XI. Data were collected through a questionnaire about first aid actions. The results showed that 47% of respondents had adequate first aid knowledge, 46% had good knowledge, and 7% had poor knowledge. In conclusion, the majority of students at SMA Mujahidin Pontianak have adequate knowledge of first aid.